2012
DOI: 10.1080/09593330.2011.630422
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extraction solutions on carbonation of cementitious materials in aqueous solutions

Abstract: Carbonation efficiency was evaluated for three cementitious materials having different CaO-bearing minerals (lime, Portland cement and waste concrete) using various extraction reagents (HCl, CH3COOH, NH4Cl and deionized water). The cementitious materials were subjected to Ca extraction and carbonation tests under ambient pressure and temperature conditions. The Ca extraction efficiency generally decreased in the order lime, Portland cement and waste concrete, regardless of the extraction solution. Among the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The 1 M NH 4 Cl solution was prepared by dissolving 1 mol NH 4 Cl (Junsei Chemical Co., Ltd.) in 1 L of solution. Several studies have shown that NH 4 Cl is an effective solvent for mineral carbonation of CO 2 using alkaline wastes [18,27]. Seawater collected from a coastal region was used, as in Korea seawater is usually mixed with CFA from CFPPs and the mixture is then sluiced into the coal ash pond.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1 M NH 4 Cl solution was prepared by dissolving 1 mol NH 4 Cl (Junsei Chemical Co., Ltd.) in 1 L of solution. Several studies have shown that NH 4 Cl is an effective solvent for mineral carbonation of CO 2 using alkaline wastes [18,27]. Seawater collected from a coastal region was used, as in Korea seawater is usually mixed with CFA from CFPPs and the mixture is then sluiced into the coal ash pond.…”
Section: Methodsmentioning
confidence: 99%
“…Alkali-rich natural rocks and alkaline industrial wastes with high Ca or Mg contents have been extensively evaluated as raw materials for mineral carbonation [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Using alkaline industrial wastes has the following advantages over natural rocks: (1) Ca or Mg bearing minerals are easily obtained from industrial wastes without preprocessing; (2) industrial wastes usually have high fine content, resulting in high reactivity with CO 2 ; (3) industrial wastes formed under high temperature conditions are generally thermodynamically unstable and thus have a high dissolution capacity; Table 1 Physical properties and chemical composition of CFA and reagent grade CaO (from Jo et al [17] gas; (3) no energy input required to crush reactants or to elevate temperature or pressure [17]; (4) CO 2 sequestration is conducted near to the CFPP; and (5) beneficial reuse of the products land-filled as aggregates in concrete and backfill materials.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon might be interpreted as a stabilization of the final solution pH around 8.0, due to continuous proton production by a significant amount of un-solvated CO2 gas, even though the gas injection was stopped at solution pH 8.5. Chang et al [36] reported that a higher CO2 flow rate decreased carbonation conversion due to poor CO2 mass transfer between gas and liquid phases; hence, the increase in Ca ions in solution with the dissolution of CaCO3 at a pH of approximately 8.0 [37]. Consequently, under high gas flow conditions, gas injection control is crucial for targeting the final solution pH to avoid re-dissolution of CaCO3.…”
Section: Physicochemical Characteristics Of the Samplementioning
confidence: 99%
“…Previous researches regarding aqueous mineral carbonation have mainly focused on enhancing the leaching efficiency of alkaline earth metals by pre-treating raw materials before carbonation processes [4,[5][6][7][8]. Natural alkaline materials and alkaline industrial wastes have been extensively evaluated for the mineral carbonation, e.g., [8,[9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…However, the major challenge of the mineral carbonation method is to enhance the leaching capacity of alkaline earth metals from raw materials, which is a main factor affecting rate and degree of mineral carbonation [3,4]. The leaching processes of alkaline earth metals from raw materials are generally expensive due to the need for increasing temperature and pressure, acid or base solutions, and grinding raw materials.…”
Section: Introductionmentioning
confidence: 99%